2018
DOI: 10.1111/jvim.15231
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Dogs with Biofilm‐Forming Escherichia Coli Urinary Tract Infections

Abstract: BackgroundBacterial urinary tract infections (UTIs) are common in companion animals. Increasing awareness of biofilm‐forming bacteria raises concern regarding the appropriate diagnosis, treatment, and prognosis of UTIs associated with these organisms.Hypothesis/ObjectivesTo (1) describe the population of dogs with UTIs associated with biofilm‐forming Escherichia coli and (2) determine whether or not clinical differences exist between dogs with biofilm‐forming E. coli UTIs and dogs with nonbiofilm‐forming E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…It is suggested to be responsible for about 80% of all chronic human infections [ 48 ]. However, the role of biofilm formation in animal infections is not well understood, since biofilm studies in animals are uncommonly reported, and most studies conducted so far focus mainly on bovine mastitis [ 37 , 49 ]. Animal-adapted S. aureus has different characteristics and may behave differently from human S. aureus , for example, S. aureus ST398 in animals are usually associated with methicillin- and tetracycline-resistance [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested to be responsible for about 80% of all chronic human infections [ 48 ]. However, the role of biofilm formation in animal infections is not well understood, since biofilm studies in animals are uncommonly reported, and most studies conducted so far focus mainly on bovine mastitis [ 37 , 49 ]. Animal-adapted S. aureus has different characteristics and may behave differently from human S. aureus , for example, S. aureus ST398 in animals are usually associated with methicillin- and tetracycline-resistance [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…While our findings show higher percentages of biofilm formation at 24 hours compared to a previous survey among canines, our prevalence of biofilm formation aligned with a previous study of urinary associated E . coli using a similar methodology [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggests that UPEC may mix-and-match virulence traits to express biofilm phenotypes. Similarly, certain antimicrobial resistance phenotypes and genes, particularly those that confer fluoroquinolone resistance, have been associated with biofilm formation [ 10 , 13 ]. However, the relationship between AMR and biofilms is inconsistently reported across the literature and suggest that the true relationship is unknown [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli are known to produce and maintain biofilm that acts as a shield to protect the colonizing flora (Silva et al, 2014), and here, biofilm formation was evident in all the 57 isolates. Although some authors claim that biofilm production has a negligible bearing upon drug resistance (Kern et al, 2018), others concluded biofilm as an important tool for chronic infection and pathogenicity maintenance, directly affecting the morbidity of patients with chronic bacterial diseases (Clinton & Carter, 2015; Ponnusamy et al, 2012). A recent study conducted by our group has also established a strong correlation between biofilm production and multidrug resistance (Banerjee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%